Preventing teenage pregnancy in developing countries: a scoping review - Ratnasari, Desi; Sulistyaningsih, Sulistyaningsih (BKM Public Health and Community Medicine, 2023)
Purpose: This study aimed to determine the most recent attempts to reduce teen pregnancies in low-income nations. Methods: This scoping review used the PRISMA-ScR checklist, PEO framework, and Critical Appraisal for assessment. Data were obtained from Pubmed, Science Direct, Wiley, and Ebsco databases. Results: The researcher discovered 2,536 pertinent articles, but only ten met the inclusion criteria, which included three themes: Teenage pregnancy-related factors, health initiatives to prevent them, and educational media. Conclusion: Local laws, sex education in schools, parenting workshops, evidence-based youth programs, school reproductive health care, and instructional initiatives employing online media are all part of efforts to prevent adolescent pregnancy in developing nations.